Acting Now to Protect the Human Capital of Our Children : The Costs of and Response to COVID-19 Pandemic’s Impact on the Education Sector in Latin America and the Caribbean - World Bank (World Bank, Washington, DC, 2021)
The sanitary and economic shocks caused by the COVID-19 pandemic brought about the most significant disruption in the history of the education sector in Latin America and the Caribbean region, leading to school closures at all levels and affecting over 170 million students throughout the region. Despite the tremendous efforts made by countries to mitigate the lack of in-person education through remote learning, education is taking a serious hit and outcomes are plummeting in the region. Learning poverty by the end of primary education could increase by more than 20 percent. Over 2 in 3 lower secondary education students could fall below minimum proficiency levels, and learning losses will be substantially larger for the most disadvantaged students. There is no time to lose. All countries must act now to make sure schools are ready to reopen safely and effectively country-wide so as to speed up the recovery process from the dramatic effects of the pandemic. They can leverage many emerging lessons and evidence, and must protect public funding for education, to enable this reopening process. While education systems face a challenge like no other, this exceptionally difficult situation also opens a window of opportunity to build back better their education systems to become more effective, equitable and resilient.